solve the equation 5y-y+1by3=6y+1by 5
Answers
Answered by
0
Answer:
5y - y + 1/3 = 6y + 1/5
=> 4y + 1/3 = 6y + 1/5
=> 1/3 - 1/5 = 6y -4y
=> (5 - 3)/15 = 2y ( taking lcm)
=> 2/15 = 2y
=> y = 1/15
If the question is 5y - (y+1)/3 = 6y + 1/5
=>{ 15y - ( y + 1)}/3 = (30y + 1)/5 ( taking L.C.M)
=> (15y - y - 1)/3 = (30y + 1) /5
=> ( 14y - 1) * 5 = (30y + 1) * 3
=> 70y - 5 = 90y + 3
=> 20y = -8
=> y = -8/20
=> y = -2/5
Hope this helped you!
make me as briliantlist
Similar questions
Social Sciences,
5 months ago
Math,
5 months ago
Math,
11 months ago
Math,
11 months ago
Chemistry,
1 year ago